2020
DOI: 10.1111/pin.13039
|View full text |Cite
|
Sign up to set email alerts
|

Gastritis cystica profunda is associated with aberrant p53 and Epstein–Barr virus in gastric cancer: A clinicopathological, immunohistochemical and in situ hybridization study

Abstract: Gastritis cystica profunda (GCP) is a lesion characterized by cystic gastric glands within the submucosa. Some studies have reported that GCP is a precancerous lesion. Here, we investigated the association between GCP and gastric cancer. Gastric cancer specimens were taken from 1432 patients undergoing surgery or endoscopic submucosal resection and were classified as GCP or non‐GCP. The clinicopathological features, immunohistochemistry and in situ hybridization expression of p53, Ki‐67, KCNE2, Epstein–Barr vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 38 publications
(100 reference statements)
0
10
0
1
Order By: Relevance
“…Previous research studies with small sample sizes have revealed similar ndings. However, no signi cant differences were observed 6, 10,11 . The present study demonstrated that the survival time of EBV positive patients was longer than that of EBV negative patients.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…Previous research studies with small sample sizes have revealed similar ndings. However, no signi cant differences were observed 6, 10,11 . The present study demonstrated that the survival time of EBV positive patients was longer than that of EBV negative patients.…”
Section: Discussionmentioning
confidence: 81%
“…Its infection rate in humans can reach 90% or higher 5,8,[10][11][12][13][14] . At present, the mechanism of the EBVmediated gastric mucosal epithelium infection has been described as follows: Initially, EBV infects B lymphocytes and oral epithelial cells; subsequently, EBV is reactivated in B lymphocytes in the stomach and released to infect epithelial cells 5, 8, 10-14 .…”
Section: Discussionmentioning
confidence: 99%
“…These rare causes include: Crohn's disease, eosinophilic gastroduodenitis, systemic mastocytosis, vasculitis and ischemia, as well as tumours (e. g. gastrinomas), metastases and other consuming diseases. In immunocompromised or immunosuppressed patients (HIV infection, after organ transplan-tation), viral infections or reactivations (CMV, EBV, HSV) with gastroduodenal ulcers occur more frequently [563][564][565][566]. Increased exposure to radiation from a previous radiotherapy or internal radiotherapy (e. g. as part of selective internal radiotherapy (SIRT)) can cause gastrointestinal ulcers throughout the gastrointestinal tract [567][568][569][570][571][572].…”
Section: [Recommendation Strong Consensus]mentioning
confidence: 99%
“…B. Gastrinome), Metastasen und andere konsumierende Erkrankungen. Bei immunkompromittierten oder immunsuppressiv behandelten Patienten (HIV-Infektion, nach Organtransplantation) treten gehäuft virale Infektionen oder Reaktivierungen (CMV, EBV, HSV) mit gastroduodenalen Ulzera auf [562][563][564][565]. Eine erhöhte Exposition im Strahlenfeld einer erfolgten Radiotherapie oder durch interne Radiotherapie (z.…”
Section: Leitlinieunclassified